Detection of macrophages in aortic aneurysms by nanoparticle PET-CT - Nahrendorf, Matthias (2011)
OBJECTIVE: Current management of aortic aneurysms (AAs) primarily relies on size criteria to determine whether invasive repair is indicated to preempt rupture. We hypothesized that emerging molecular imaging tools could be used to more sensitively gauge local inflammation. Since macrophages are key effector cells that destabilize the extracellular matrix in the arterial wall, it seemed likely that they would represent suitable imaging targets. We here aimed to develop and validate macrophage-targeted nanoparticles labeled with fluorine-18 ((18)F) for PET-CT detection of inflammation in AAs. METHODS AND RESULTS: Aneurysms were induced in apoE(−/−) mice via systemic administration of angiotensin-II. Mice were imaged using PET-CT and a monocyte/macrophage-targeted nanoparticle. AAs were detected by contrast-enhanced micro-CT and had a mean diameter of 1.85 ± 0.08 mm, whereas normal aortas measured 1.07 ± 0.03 (p < 0.05). The in vivo PET signal was significantly higher in aneurysms (SUV 2.46 ± 0.48) when compared to wild type aorta (0.82 ± 0.05, p<0.05). Validation with scintillation counting, autoradiography, fluorescence and immunoreactive histology and flow cytometry demonstrated that nanoparticles predominantly localized to monocytes and macrophages within the aneurysmatic wall. CONCLUSIONS: PET-CT imaging with (18)F-CLIO (cross-linked iron oxide) nanoparticles allows quantitation of macrophage content in a mouse model of AAs.